Use of modern computer technologies in the professional training of future engineers-educators - Onyshchenko, Serhii (DEL c.z., 2023)
Modern computer technologies in education make it possible to more actively use the scientific and educational potential of leading universities and institutes, to attract the best teachers to the creation of distance learning courses, and to expand the audience of students.